REGISTER PEDAGANG DI PASAR KLITHIKAN LESTARI MULYO KANGGOTAN, PLERET, BANTUL, YOGYAKARTA - Riza Ardhian Mustainullah; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study is (1) to describe the form of registers, (2) the function of registers, and (3) to describe the meanings of specific terms at traders' registers at the Klithikan Lestari Mulyo Kanggotan, Pleret, Bantul, Yogyakarta markets. This type of research is a qualitative descriptive study. The sources of this research are traders in the Klithikan Lestari Mulyo market. Data obtained by using the method of observation / refer to the method of sequel, namely free speech, conversation and using data collection techniques record techniques and note-taking techniques. Data were analyzed by translational equivalent method with the basic technique of determining the determinant elements and the subsequent technique using translational computational power. The method of presenting the results of data analysis uses an method informal data. The results of this study are as follows. (1) The forms of traders' registers in the Klithikan Lestari Mulyo Kanggotan, Pleret, Bantul, Yogyakarta markets are (a) single-word form registers (b) complex word-form registers, including affixed and compound words. (2) The register function of traders in the Klithikan Lestari Mulyo Kanggotan, Pleret, Bantul, Yogyakarta markets includes (a) instrumental functions, (b) interaction functions, (c) healer / problem solving functions (d) information functions. (3) The specific meaning of the register trader at the Klithikan Lestari market, Mulyo Kanggotan, Pleret, Bantul, Yogyakarta. The meaning of a specific term is marked with words that are general but have a special meaning.